Loyalitas Petani Dalam Melakukan Pembelian Benih Padi Produksi PP Kerja Di Solo Raya - Gresia Rahmawati; Mohd. Harisudin; Hanifah Ihsaniyati (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
The purpose of this research are   (1) to know the influence   of product quality, price, service quality toward the customer satisfaction PP Kerja and (2) to know the influence of product quality, price, service quality and customer satisfaction toward the PP Kerja’s customer loyalty. The research here used explanatory research in this research. The sample used by 50 farmers who are customers of PP Kerja. The sampling technique using Convenience Sampling. Data were collected by questionnaire. The technique of collecting data was solved through observation, interviews and recording. Analysis of the data used is descriptive analysis and path analysis (path analysis). The results of this research showed that (1) the product quality  (X1),  price  (X2)  and  service  quality  (X3)  simultaneously  influenced  the customer satisfaction of PP Kerja (Y1). The total influenced of each variabel is 0,339;0.178 and 0.543. (2) the product quality (X1), price (X2), service quality (X3) and customer satisfaction (Y1) simultaneously influenced the customer loyalty of PP Kerja (Y2). The price variable could influence the total of customer satisfaction 0,222; the service quality variable 0,362 and the customer satisfaction variable 0,442 it could give influence toward the customer satisfaction.